Urge To Buy Impulsively Among Generation Z: The Influence Of Visual Appeal And Portability With Hedonic Browsing As A Mediating Variable - Fakhriyah, Widya Shafanisa; Ismail, Taufiq (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
To improve the effectiveness of marketing strategies, it is essential to understand the factors that drive impulsive behavior, such as visual appeal and portability. This quantitative explanatory study investigates the influence of visual appeal and portability on the urge to buy impulsively on the Shopee application, with hedonic browsing as a mediating variable. Using a non-probability sampling method with judgment sampling, 130 Generation Z Shopee users were selected as respondents. The data were collected through an online questionnaire and analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS to examine the relationships among variables and determine their structural positions. Through outer model testing, inner model testing, and hypothesis testing, this study reveals that (1) hedonic browsing has a significant positive effect on the urge to buy impulsively, (2) visual appeal and (3) portability significantly and positively affect hedonic browsing, (4) visual appeal has a significant positive effect on the urge to buy impulsively, and (5) hedonic browsing mediates the indirect effect of visual appeal on the urge to buy impulsively. These findings enable marketers and e-commerce developers to optimize the visual appeal and portability of applications to create an enjoyable shopping experience that encourages impulsive purchasing behavior.